Influence of quuertulin on ultrastructure of mucous membrane of colon of rats that got over-oxidized sunflower oil (electronic-microscopic research) - Bocharov, Andrew; Levitsky, Anatoly; Molchanuk, Nataly; Makarenko, Olga (Journal of Education, Health and Sport, 2019)
Aim: To study the ultrastructure of the crypts of the mucosa of the colon of rats, a long time food content peroxidation sunflower oil and to determine the possible preventive effects on ultrastructure of the cover complex antidysbiosis hepatoprotector Quertulin (quercetin + inulin + calcium citrate)Methods: Fragments of the mucous membrane of the colon taken from 9 rats of the Wistar, were divided into 3 groups: 1- intact animals, 2 - receiving (per os) 1 ml over-oxidized sunflower oil for 75 days, 3 - receiving over-oxidized sunflowers oil with the addition Quertulin 300 mg/kg from 31 to 75 days. Studied ultrastructural shell colon in electron microscopic TEM-100 - 01.Results: In rats that received over-oxidized sunflower oil with food for 75 days. Electron microscopy revealed that the apical surface of columnar cells of the crypt of the mucous membrane of the colon has a disturbed plasmolemma, reduced microvilli, the pathological state of individual mitochondria. In its own plate of the mucous membrane there are large electron-transparent patches, indicating the edema of the basic substance. Rats that received the diet over-oxidized sunflower oil and antidysbiosis hepatoprotector Quertulin (quercetin + Inulin + calcium citrate) 300 mg / kg daily, columnar cells without disturbances, tight contact with each other. In the cytoplasm of these cells, there is an increased amount of organelles (ribosomes, mitochondria), the Golgi complex is expressed clearly. And, although in some places there are areas in the mucosal crypts in which columnar cells are destroyed the plasmolemma, but in the cytoplasm contains many mitochondria with electron-dense matrix and clear crypts.Conclusion: The results of an electron microscopy study showed that after administration of over-oxidized sunflower oil to rats, the structure of the mucous membrane in large areas is significantly damaged. The treatment with Quertulin in rats greatly contributes not only to the restoration of the ultrastructure of the mucous membrane of the large intestine of rats, but also greatly enhances the metabolic processes in them.